Study on a solid slow dissolution sphere with corrosion inhibition. Issue 5 (July 2020) - Guo, Ruhui; Zhang, Lihui; Yan, Meifang; Liu, Zhan; Sun, Lijing
Abstract: Many substances with excellent corrosion inhibition can't be dissolved into aqueous solution according to the amount required by the formulation due to poor solubility, thus reducing the corrosion inhibition effect of the agent. Therefore, a spherical solid corrosion inhibitor has been developed. The effect of dosage and temperature on the corrosion inhibition rate was studied by corrosion test. The results showed that the best dosage of corrosion inhibition ball was 28.5mg/l, and the corrosion inhibition rate decreased with the increase of temperature. When the water temperature was 35 °C, 45 °C and 55 °C, the corrosion rates of carbon steel were 0.0243mm/a, 0.0306mm/a and 0.0559mm/a, which were lower than the national standard 0.075 mm / a indicating that the inhibitor has good corrosion resistance.